Genome-Wide Association Study of Calcium Accumulation in Grains of European Wheat Cultivars - Alomari, Dalia Z.; Eggert, Kai; von Wirén, Nicolaus; Pillen, Klaus; Röder, Marion S. (Frontiers in Plant Science, 2017)
Mineral concentrations in cereals are important for human health, especially for people who depend mainly on consuming cereal diet. In this study we carried out a genome-wide association study (GWAS) of calcium concentrations in wheat (Triticum aestivum L.) grains using a European wheat diversity panel of 353 varieties (339 winter wheat (WW) plus 14 of spring wheat (SW)) and phenotypic data based on two field seasons. High genotyping densities of single nucleotide polymorphism (SNP) markers were obtained from the application of the 90k iSELECT ILLUMINA chip and a 35k Affymetrix chip. Inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to measure the calcium concentrations of the wheat grains. Best linear unbiased estimations (BLUEs) for calcium were calculated across the seasons and ranged from 288.2 to 647.5 among the varieties (µg g-1DW) with a mean equaling 438.102 (µg g-1DW), and the heritability was 0.73. A total of 485 SNP marker–trait associations (MTAs) were detected in data obtained from grains cultivated in both of the two seasons and BLUE values by considering associations with a −log10 (P-value) ≥3.0. Among these SNP markers, we detected 276 markers with a positive allele effect and 209 markers with a negative allele effect. These MTAs were found on all chromosomes except chromosomes 3D, 4B and 4D. The most significant association was located on chromosome 5A (114.5 cM) and was linked to a gene encoding cation/sugar symporter activity as a potential candidate gene. Additionally, a number of candidate genes for the uptake or transport of calcium was located near significantly associated SNPs. This analysis highlights a number of genomic regions and candidate genes for further analysis as well as the challenges faced when mapping environmentally variable traits in a genetically highly diverse variety panels. The research demonstrates the feasibility of the GWAS approach for illuminating the genetic architecture of calcium-concentration in wheat grains and for identifying putative candidate genes underlying this trait.